2019
DOI: 10.1002/adom.201801682
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of Third‐Harmonic Generation in Organic Cavity Polaritons

Abstract: exchange of energy between excitons and photons is faster than any loss process. The momentum-energy dispersions of cavity polaritons are characterized by anticrossing of the exciton and cavity dispersions consisting of an upper-polariton (UP) branch (UPB) and a lower-polariton (LP) branch (LPB), with the minimal energy separation between UPB and LPB at the anticrossing point referred as the vacuum Rabi splitting energy (ℏΩ R ). [1] Due to the large oscillator strength and binding energy of organic materials, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
45
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 40 publications
5
45
2
Order By: Relevance
“…To our knowledge, this last value is the first Rabi splitting for a solid-state system to reach a value comparable to photons in the visible spectrum (∼ 689 nm), exceeding by more than 60% the previous record. 14,15 The corresponding coupling ratio g ∼ 65% is also slightly higher than that reported in Ref 25, a notable result given that the g-value reported here was obtained for an exciton lying some ∼ 1.6 eV higher in energy. The results for TM polarization for the aligned polymer cavities are shown in Figure 4 (b), (c) and (d).…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…To our knowledge, this last value is the first Rabi splitting for a solid-state system to reach a value comparable to photons in the visible spectrum (∼ 689 nm), exceeding by more than 60% the previous record. 14,15 The corresponding coupling ratio g ∼ 65% is also slightly higher than that reported in Ref 25, a notable result given that the g-value reported here was obtained for an exciton lying some ∼ 1.6 eV higher in energy. The results for TM polarization for the aligned polymer cavities are shown in Figure 4 (b), (c) and (d).…”
Section: Resultscontrasting
confidence: 54%
“…7 Their large intrinsic oscillator strengths 8 combined with the small mode volumes V m of metallic microcavities 9 have enabled Ω R ≥ 1 eV, [10][11][12][13] with values up to Ω R = 1.12 eV. 14,15 This splitting is directly comparable to the exciton transition energy ω ex and yields normalized coupling ratios g = Ω R ωex ≥ 20%, thereby crossing into ultrastrong coupling (USC), an interaction space that has received great recent attention, with attractive research perspectives and multiple emerging applications. 16,17 Experimental realizations of increasingly higher coupling ratios have also been reported for inorganic semiconductor based intersubband polaritons, 18 and other physical systems, including superconducting circuits, 19 Landau polaritons 20 and plasmonic picocavities interacting with vibrational degrees of freedom of individual molecules.…”
mentioning
confidence: 99%
“…For instance, strongly coupled organic molecules could enhance the conductivity 15,16 , the rate of energy transfer 17 of molecules, and furthermore, modify the work function 18 and chemical reactions of molecules 19,20 . Besides, recent studies also showed that second-harmonic generation and third harmonic generation could be enhanced in the presence of polaritonic states [21][22][23][24] . However, the measurements in these works did not characterize the intrinsic nonlinear optical parameters such as n 2 and β, which are necessary to evaluate the true potential of strong coupling for all nonlinear optical processes.…”
mentioning
confidence: 99%
“…intersystem crossing,[22][23][24] non-linear optics[25][26][27][28] in addition to chemical reactivity 7,9,[29][30]. Many…”
mentioning
confidence: 99%